2022
DOI: 10.1371/journal.pone.0264437
|View full text |Cite
|
Sign up to set email alerts
|

Comparative safety and efficacy of low- or moderate-intensity statin plus ezetimibe combination therapy and high-intensity statin monotherapy: A meta-analysis of randomized controlled studies

Abstract: Statin is highly recommended for dyslipidemia to prevent atherosclerosis-related cardiovascular diseases and death. The aim of this study was to compare the efficacies and safeties of low/moderate-intensity statin plus ezetimibe combination therapy vs. high-intensity statin monotherapy. Meta-analysis was conducted on data included in published studies performed to compare the effects of the two treatments on lipid parameters and hs-CRP. Safety-related parameters were also evaluated. Eighteen articles were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…This finding supported results of clinical trials that demonstrated a favorable effect of adding ezetimibe to statin therapy on cardiovascular events in patients with an acute coronary syndrome [44] . While addition of ezetimibe to low or moderate intensity statin therapy may be better tolerated and produce greater lipid lowering than high intensity statin alone [45] , further studies are required to evaluate the impact of these strategies on coronary atheroma.…”
Section: Ezetimibementioning
confidence: 99%
“…This finding supported results of clinical trials that demonstrated a favorable effect of adding ezetimibe to statin therapy on cardiovascular events in patients with an acute coronary syndrome [44] . While addition of ezetimibe to low or moderate intensity statin therapy may be better tolerated and produce greater lipid lowering than high intensity statin alone [45] , further studies are required to evaluate the impact of these strategies on coronary atheroma.…”
Section: Ezetimibementioning
confidence: 99%
“… 175 177 Adding ezetimibe to statin treatment significantly decreases the risk of cardiovascular events and further reduces residual risk in patients already receiving maximally or maximally tolerated statin remedy and in patients with diabetes. 178 180 Similarly, involving an inhibitor of protein convertase subtilisin/kexin type 9 (PCSK9) to statin treatment, which can lower plasma LDL levels, demonstrated good therapeutic effects. 181 Compared to statin treatment alone, the combination strategy reduced LDL levels by over 50%.…”
Section: Atherosclerosis (As)mentioning
confidence: 99%
“…Regarding safety, there were no significant differences between the two treatments regarding ALT elevation, but high-intensity statin therapy led to a significant increase in AST and CK compared to combination therapy [ 20 ]. Another study highlighted that adherence to moderate-intensity statins plus ezetimibe therapy may be higher compared to high-intensity statin therapy.…”
Section: Reviewmentioning
confidence: 99%
“…The present meta-analysis does not identify any statistical differences concerning cardiovascular outcomes between the two treatment groups. However, it acknowledges that prior meta-analyses have demonstrated the significant impact of combination therapy on lipid profiles and other biomarkers [ 20 ]. Essentially, while the current study does not observe a statistical advantage, it acknowledges the existing evidence from previous research suggesting benefits in terms of lipid profile and other biomarkers associated with combination therapy.…”
Section: Reviewmentioning
confidence: 99%